Green synthesis of silver nanoparticles by tualang honey modulating Hippocampal glutathione in kainic acid-induced seizure in male rats - Hasim, Hidani; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Visweswara Rao, Pasupuleti; Muthuraju, Sangu; Asari, Mohd Asnizam (2022)
In recent years, green synthesis of nanoparticles using plant-mediated process has been an emerging research and development in the field of medicinal biotechnology. Tualang honey, a potential natural antioxidant medicinal agent, has been shown to protect against neurodegenerative disorders. Present study explored the ameliorative effects of silver nanoparticles (AgNPs) synthesized using Tualang honey on glutathione level following kainic acid (KA)-induced seizure in the rats' hippocampus. Sprague Dawley male rats (n=42) were randomly divided into seven groups such as control, AgNPs 10 mg,AgNPs50mg, KA alone, AgNPs 10 mg+KA, AgNPs 50 mg+KA and Topiramate+KA, and each group were pre-treated orally with either distilled water, AgNPs (10 mg/kg or 50 mg/kg) or Topiramate (40 mg/kg), respectively, five times at 12 h intervals. Saline or KA (15 mg/kg body weight) were injected subcutaneously 30 min after last oral treatment. All animals were sacrificed 24 h after KA injection and their hippocampus were harvested for determination the level of reduced glutathione (GSH), oxidized glutathione (GSSG) and GSH:GSSG ratio by using commercially available ELISA kits. The significant(p<0.05) decrease in the level of GSH in KA alone group was ameliorated by both doses of AgNPs pre-treatments. Meanwhile, the elevation of GSSG level in KA alone group was significantly(p<0.05)reduced by the pre-treatments of AgNPs 10 mg and Topiramate of KA-induced groups. Remarkably, only AgNPs 1 0+KA group was significantly (p<0.05) increases the GSH:GSSG ratio after KA induced. In conclusion, AgNPs showed potential protective effects by modulating the glutathione system in the rats hippocampus after KA induced.